Recent Developments in the Synthesis of 2‐C‐Branched and 1, 2‐Annulated Carbohydrates. Issue 35 (9th November 2015) - Vankar, Yashwant D.; Linker, Torsten
Abstract: The importance of carbohydrate chemistry in biological and medicinal chemistry has led to enormous developments in the synthesis of carbohydrate mimics. In this context, the synthesis of branched sugars in general and of 2‐ C ‐branched carbohydrates in particular, as well as the synthesis of 1, 2‐annulated sugars, have received immense attention. They serve not only as carbohydrate mimics in the form of stand‐alone molecules, but also as useful intermediates in the synthesis of many natural products, their analogues, and glycosidase inhibitors. This microreview covers the recent synthetic efforts in this area and puts the subject matter into proper perspective for future developments. Abstract : This microreview highlights the recent developments in the synthesis of 2‐ C ‐branched and 1, 2‐annulated carbohydrates2 and3, respectively, during the last four years. The transformations proceed with high regio‐ and stereoselectivities, and the carbohydrate analogues2 and3 serve as precursors for biologically important compounds and several natural products.